Proportion of Chromosomal Disorders and Their Patterns among Births with Congenital Anomalies in Africa: A Systematic Review and Meta-Analyses - Teshome Gebremeskel Aragie; Girma Seyoum Gedion (The Scientific World Journal)
Introduction. Worldwide, surveys have shown that the frequency of chromosomal disorders among births with congenital anomalies varies greatly from country to country. It is well known that chromosomal disorders are an important cause of premature death or life-long disability; however, the absence of local epidemiological data on their birth prevalence and outcomes impedes policy and service development in many countries and continents. Therefore, the current systematic review and meta-analysis intend to show the pooled proportion of chromosomal disorders among births with congenital anomalies in Africa. Methods. From PubMed, Cochrane Library, and Google Scholar, we systematically reviewed and meta-analyzed the studies that examined the incidence, prevalence, and types of chromosomal disorders using PRISMA guidelines. A weighted inverse variance random-effects model was used to estimate the pooled proportion of chromosomal disorders among births with congenital anomalies. Results. From the total of 3,569 studies identified, 1,442 were from PubMed, 108 were from Cochrane Library, 1,830 were from Google Scholar, and 189 were from other sources. After duplication was removed, a total of 844 articles remained (2725 were removed by duplication). Finally, 144 full-text studies were reviewed and 60 articles with 52,569 births having congenital anomalies met the inclusion criteria and were selected for this meta-analysis. The pooled proportion of chromosomal disorders among births with congenital anomalies was 8.94% (95% CI; 7.02, 10.86; I2 = 98.8%; p<0.001). Conclusions and Future Implications. In the current systematic review and meta-analysis, the pooled proportion of chromosomal disorders among births with congenital anomalies in Africa was small. Down syndrome (trisomy 21) accounted for more than 80% of chromosomal disorders. The pooled proportion of chromosome disorders was the highest in North African regions and countries compared to other regions of the continent. Healthcare managers should focus on establishing proper cytogenetic diagnostic facilities in collaboration with well-trained genetic counseling services in the continent.